Canada jays (Perisoreus canadensis) identify and exploit coniferous cache locations using visual cues. (23rd February 2022) - Martin, R. Jeff; Fuirst, Matthew; Sherry, David F.
Abstract: Food caching is a foraging strategy used by many vertebrates, involving the storage and subsequent recovery of food items for later consumption, when other food sources are scarce. Once cached, stored food, particularly highly perishable items, can degrade over time. Evidence suggests that for birds, some conifers may aid in cache preservation through protective properties in resin. However, due to the challenges involved with following birds to their caching locations, cache‐site preferences are not easily studied in the wild. We investigated eight captive Canada jays' ( Perisoreus canadensis ) ability to both identify and exploit conifer tree species. Further, we examined potential cues that birds may use to identify and select these potentially beneficial sites. We found strong evidence to suggest that birds can quickly identify conifer tree species and subsequently exploit those cache locations preferentially. Furthermore, our evidence suggests that although birds do not appear to use olfactory cues when making caching decisions, they potentially to attend to structural cues. We suggest that visual information is essential to both the identification of conifer trees and to cache‐site selection decisions. These findings indicate that jays make rapid, fine scale assessments of their environments, discriminating amongst trees of different species and use this information to select cache‐sites. Abstract : Canada jays quickly identify beneficial tree species for caching (A). Once identified, Canada jays disproportionally perch (B) and cache (C‐E) in these trees when compared to trees that are not considered beneficial. These findings indicate that jays make rapid, fine scale assessments of their environments, discriminating amongst trees of different species and use this information to select cache‐sites.